QRIS and the Future of Digital Payments: Factors Influencing Consumer Behavioral Intentions in Indonesia - Susanti, Melly; Santi, Fitri; Robinson , Robinson (Westscience Press, 2025)
This study aims to identify the factors that influence consumer behavioral intention in adopting the Quick Response Indonesian Standard (QRIS) mobile payment system in Indonesia. Using a quantitative research design, data was collected through questionnaires distributed online to QRIS users. This study explores the influence of individual factors, alternatives, and behavioral intentions on QRIS adoption. The analysis results show that individual factors, such as personal knowledge and innovativeness, have a significant influence on consumers' behavioral intention to adopt QRIS. In addition, the attractiveness of other payment alternatives, such as cash and credit cards, also influence the adoption decision. Consumer behavioral intention is shown to be an important factor in the decision to use QRIS. This research contributes to enriching the literature on digital payment technology adoption and provides strategic recommendations to increase QRIS adoption in Indonesia, including through increasing consumer education, building trust, and strengthening the advantages of QRIS over other alternatives.